English Language Training for Local Community in the Tourism Site of Karang Talun Mangrove Forest, Cilacap, Central Java - Betti Widianingsih; Dodi Satriawan; Fadhillah Hazrina; Novita Asma Ilahi; Riyani Prima Dewi; Devi Taufiq Nurrohman (Universitas Muhammadiyah Sidoarjo, 2021)
Mangrove Forest which is located at Karang Talun village, Tritih Kulon sub-district, North Cilacap, Central Java has a various potentials to develop. Its development can be conducted by utilizing local community for participating to improve with mastery of English language. Thus, it is necessary to conduct empowerment of local community through English language training to create qualified ones who can support in tourism field. The purpose of this training is to improve their English language skill and increase their economy and be able to survive by being local tour guide in the New Normal. There were 15 participants consist of traders and some employees who work in Mangrove forest. It was conducted for three days and used some methods, namely preaching method i.e, giving theory and practice learning on each unit of learning and drilling and repetition method. In addition, they were given pre test and post test to evaluate each participant’s skill. From the result, the participant’s skill in pronunciation, vocabulary and practicing dialogue has improved, but it still needs more practices. Drilling and repetition method in learning activity has been success to be applied for participants